2014
DOI: 10.3390/rel5041132
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping, Social Support and Subjective Severity as Predictors of Posttraumatic Growth in People Affected by the Earthquake in Chile on 27/2/2010

Abstract: Abstract:The aim of this research is to study the impact of religious coping, social support and subjective severity on Posttraumatic Growth (PTG) in people who lost their homes after the earthquake in Chile in 2010 and who now live in transitional shelters. One hundred sixteen adult men and women were evaluated using a subjective severity scale, the Posttraumatic Growth Inventory (PTGI), the Multidimensional Scale of Perceived Social Support (MSPSS) scale of social support and the Brief RCOPE scale of religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
5
30
0
5
Order By: Relevance
“…Also, correlations and regressions showed that positive RC was a stronger predictor of change in PTG than social support-although the role in undermining the increase of PTG by negative RC was even lower. The direct relationship and influence of positive RC with positive change in PTG corroborates the result of other studies [8] and implies that positive RC would help to find a sense in life, providing a framework of meaning that helps to understand and accept the nature of stressing events and their consequences [1]. This has led to RC being considered as a healthy psychological adaptation to stress [46], providing additional benefits to other non-religious means of coping [10].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Also, correlations and regressions showed that positive RC was a stronger predictor of change in PTG than social support-although the role in undermining the increase of PTG by negative RC was even lower. The direct relationship and influence of positive RC with positive change in PTG corroborates the result of other studies [8] and implies that positive RC would help to find a sense in life, providing a framework of meaning that helps to understand and accept the nature of stressing events and their consequences [1]. This has led to RC being considered as a healthy psychological adaptation to stress [46], providing additional benefits to other non-religious means of coping [10].…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, Rivera and Montero obtained adequate reliability for Latin American populations for both dimensions, apart from convergence validity with other scales of religiosity. In a study performed by the authors [8] with Chilean population, an α = 0.95 was obtained for positive RC, 0.90 for negative RC, and 0.90 for negative RC.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained as negative religious coping probably evokes a persistent psychological discomfort under stress conditions and, in the specific case of health problems, it would be related to shame and guilt feelings associated with risk behaviors (Lee et al, 2014). In the Chilean population as an example, religious coping has shown a strong influence on the emotional state after a stressful event, even when perceived social support is controlled (Garc ıa, P aez, Cartes, Neira & Reyes, 2014;Garc ıa, P aez, Reyes & Alvarez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an increasing number of individual researchers have introduced the notion of religion in disaster, mainly because religion influences how people sense or manage disasters. Similarly, some international journals have begun to publish articles on the relationship between religion and disaster (or its management), such as "Religions," "Religion," "Public Health Ethics," "Disaster Prevention and Management," and others [18][19][20][21].…”
Section: Background Theoriesmentioning
confidence: 99%